Doing business 2016 : measuring regulatory quality and efficiency : comparing business regulation for domestic firms in 189 economies : a World Bank Group flagship report. - World Bank.; World Bank Group (Washington, DC : World Bank, 2016)
Doing Business 2016 is the 13th publication in a series of annual reports comparing business regulation in 189 economies. This year the publication addresses regulations affecting 11 areas of everyday business activity including: Starting a business Dealing with construction permits Getting electricity Registering property Getting credit Protecting minority investors Paying taxes Trading across borders Enforcing contracts Resolving insolvency Labor market regulations Doing Business 2016 updates all indicators as of June 1, 2015, ranks economies on their overall ease of doing business, and analyzes reforms to business regulation identifying which economies are strengthening their business environment the most. This report illustrates how reforms in business regulations are being used to analyze economic outcomes for domestic entrepreneurs and for the wider economy. It is a flagship product produced by the World Bank Group that garners worldwide attention on regulatory barriers to entrepreneurship. More than 60 economies have used the Doing Business indicators to shape reform agendas and monitor improvements on the ground. In addition, the Doing Business data has generated over 2,000 articles in peer-reviewed academic journals since its inception.
Bahan terbitan World Bank - Pesanan Penentuan - NIJUYON - 1n - 14.09.2016
Includes bibliographical references (p. 113-118).
Keywords: New business enterprises -- Statistics; Commercial law -- Statistics; Trade regulation -- Statistics; Industrial laws and legislation; Business enterprises -- Government policy